Estudos oleoquímicos e obtenção de ésteres metílicos e etílicos a partir do óleo extraído do Dipiteryx alata vog (baru) - Pereira, Nilson Roberto (2010)
This paper presents the results obtained in studies oleochemical harvest, extraction of oils, physical-chemical determinations, mass balance, income and process obtaining esters (methyl and ethyl) from the fruit oil of Dipterix alata vog (baru). As the results, the oil Baru can be considered as a promising option for producing biodiesel. Because of the studies presented here oleochemicals, have significant prospects to contextualize the oil Baru on the route of exploration and production of biodiesel. As it relates to key results: - almonds Baru showed 38.6% in oil content - the values for acid value (mg KOH / g oil) and water content (ppm) of these oils were respectively 0.69 to 0.83 and 1500 - revenues in phase volume biodiesel / glycerin separation after spontaneous transesterification reaction were 83% / 17% and 75% / 25% respectively for the methyl and ethyl routes - the income final mass of biodiesel were 88% (ethanol) and 91% (methyl) - The calculated values for the physico-chemical properties: acidity value, relative density, kinematic viscosity, water content and iodine value for the esters ( ethyl and methyl) Baru, as well as their blends (B5-B30) are present, whereas those required by the specifications within the rules (ANP, ASTM e Pr EN14214). Verification of income from the transesterification reaction of Baru oils was performed by thin layer chromatography and verification of spontaneous separation of phases. The determination of yields after chromatography (TLC) was performed by measuring the percentage volume (phase biodiesel / glycerin) and the mass balance of the main steps of the process (the fruit to the final biodiesel). Confirming the attainment of mixed esters contained in biodiesel Baru was performed by analysis by gas chromatography and absorption spectroscopy in the infrared region. The yields of biodiesel produced with the Baru oil were considered satisfactory for its production, a fact that is widely favored on the grounds of baru not be included as regular food on the table of the Brazilian.